English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

SimpLify:


-(m - n)


-(4e - 13)


-(-4e + 13)


-6(-3a + 15)


-5(x - y + 7)


13v - (3v +10)


(6s + 4) - (7s + 3)


24 - (6r - 12)


-(5.3x + 3) - (2y - 8.7)



5b - (7b + 2) + (3b + 2)


THANKS!

2006-12-18 12:49:07 · 6 answers · asked by Aaron 3 in Science & Mathematics Mathematics

6 answers

-m+n
-4e+13
4e-13
18a-90
-5x+5y-35
-39v^2-130v
-42s-46s-12

2006-12-18 12:55:20 · answer #1 · answered by Anonymous · 0 0

I will help you with half of them and you can try the rest.

1. -(m - n)

First: use distribution > take the (-) sign and multiply it by m and -n:

= -m - (-n)

Second: two negative become a positive (+):

= -m + n

2. -(4e - 13)

= -4e - (-13)
= -4e + 13

3. -(-4e + 13)

= -(-4e) - (13)
= 4e - 13

4. -6(-3a + 15)

= -6(-3a) - 6(15)
= 18a - 90

5. -5(x - y + 7)

= -5x - 5y - 5(7)
= -5x - 5y -35

2006-12-18 20:55:03 · answer #2 · answered by ♪♥Annie♥♪ 6 · 0 0

Just remember that a minus sign outside parentheses goes with both things in side and changes both their signs.

So in 24 - (6r - 12) for example

the 6r becomes negative and the minus 12 becomes plus 12

So it's 24 - 6r + 12

or 36 - 6r

2006-12-18 20:56:00 · answer #3 · answered by hayharbr 7 · 0 0

I won't answer them, but I will give you the distributive property:
a(b+c)=ab+ac
Remember that a negative in front of the brackets is like having -1.

2006-12-18 20:53:11 · answer #4 · answered by Anonymous · 0 2

-(m-n) = n-m
-(4e-13) = 13-4e
-(-4e+13) = 4e-13
Do you see the pattern?

2006-12-18 20:54:56 · answer #5 · answered by Steve A 7 · 0 0

Dude, that's a lot.

2006-12-18 20:53:13 · answer #6 · answered by yungr01 3 · 0 2

fedest.com, questions and answers